Pemodelan Luas Produksi dan Produktivitas Perkebunan Rakyat - Tangkere, Ellen Grace; Montolalu, Maya Hendrietta; Tarore, Melissa Lady Gisela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
Smallholder plantations are of great importance to commodity production and the macroeconomy in Indonesia. However, data shows a downward trend in the area and production of smallholder plantations in recent years. This is contrary to both the increasing global demand for smallholder plantation commodities and their value in the “green revolution” search for alternative energy sources to replace fossil fuels. This study aims to evaluate the production and area of smallholder plantations. There are two main questions regarding the future of smallholder plantation production that need to be answered: (1) What is the production projection for the coming years? and (2) What factors can predict crop production by smallholder plantations? Based on these two questions, the objectives of this study are formulated as follows: (1) To project smallholder plantation production in Indonesia in the coming years (2) To identify factors that can predict smallholder plantation crop production in Indonesia. The research data source is a tabulation published online by the Central Statistics Agency (BPS). Statistical analysis involves determining the distribution curve and regression modeling.